P0754FGF23 AND URINARY PHOSPHATE EXCRETION FOR ESTIMATION OF NEPHRON NUMBER: DIFFERENCES BETWEEN CHRONIC KIDNEY FAILURE AND KIDNEY TRANSPLANTATION. (6th June 2020) - Pasquali, Marzia; De Martini, Natalia; Tartaglione, Lida; Rotondi, Silverio; Catalfamo, Marta; Ceravolo, Maria Josè; Bagordo, Domenico; Mazzaferro, Sandro
Abstract: Background and Aims: Assuming that FGF23 levels correlate with phosphate excretion per nephron, nephron number can be estimated by measuring FGF23 levels and urinary phosphate excretion (FEP). Kuro-O proposed that the ratio of FEP to serum FGF23 levels should correlate with nephron number and is defined as the Nephron Index (NI). The aim of the study is calculating NI as nephron number estimation in patients affected by various degree of chronic kidney disease, both transplanted and not. Method: In 147 CRF patients kidney function, mineral metabolism biomarkers and NI were evaluated. Nephron Index was calculated following Kuro-o's equation (kuro-o 2019): N I = FEP · P s · eGFR FGF 23 Observed patients were divided into two groups: patients with CKD (noTX) and transplanted ones (TX). Results: noTX group was made up of 67 patients (40 males and 27 females) affected by CKD stages from G1 to G5. TX group was composed by 80 patient (49 males and 31 females) with various degree of CKD (G1T-G4T) showing mean graft age of 83, 2 ± 54, 8 months (range: 10, 3-268, 0). The two groups differed for age (mean age 59 ± 15, 6 years in CKD, 55± 10, 3years in TX). Mean eGFR did not differ between TX and noTX but NI was higher in TX since FEP was higher despite lower FGF23 levels in TX. The difference in FGF23 levels does not appear to depend on Klotho and PTH whose serum levels were no different between Tx and noTx. (Table1). As far as correlations are concerned, NI correlated with eGFR, FGF23, PTH and 1, 25D in both group, while NI correlated with FEP only in the TX group. It's interesting that no correlation existed between FGF23 and sP, FEP, eGFR and sKlotho in TX differently from noTX (Table2). Discussion. NI could not be properly defined as nephron number estimation in TX pts. However it may represent higher function of residual nephrons, since higher FEP did not correlate to FGF23 and could be determined by compensatory hyperfiltration (increased single nephron GFR) in transplanted patients. Conclusion: After kidney transplantation, high NI value could have a functional meaning rather than represent residual number of nephrons.